Europeism and "Complex Sovereignty" - Rocha, Acílio da Silva Estanqueiro (2019)
The scope of this reflection is to emphasize the typology and originality of European integration, in which the cosmopolitanism achieved is such that it is inaccessible to a national state, no matter how perfect its democratic structure. Although the democratic configuration of the European Union is insufficient and need further deepening, it is not only a guarantee of fundamental individual rights but also of the rights of the Member States and their peoples as collectives, supported by a “complex sovereignty” – shared by the Member States and Regions; in this way, the Union can respond to the great challenges of the 21st century – impossible by the isolated action of an isolationist sovereignty – and the resulting European identity is a post-national identity.